STRATEGI GURU PAI DALAM MEMBIMBING PESERTA DIDIK TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Beben Zuber Effendi (MGMP PAI Jawa Barat, 2022)
Education has a very basic mission, which is to form a complete human being with morals as one of the main indicators. However, the education that has been going on so far has mostly pursued the targets of formalities and curricula that have been set. This has an impact on the number of deviant behaviors carried out by students at the age of adolescents, so guidance is needed, especially PAI teachers. Therefore, PAI teachers need to have strategies in guiding students to practice the teachings of the Islamic religion in schools. This study aims to get an overview of pai teacher strategies, evaluations, supporting factors, constraints and impacts of implementing strategies carried out by PAI teachers in guiding students towards learning Islamic religious education in SMP at the Karawang City Commissariat. This research method uses a survei method by distributing the questionnaire online to 30 PAI. In addition to the questionnaire, researchers also conducted online interviews through the WhatsApp application to corroborate the survei results. The data from the distribution of questionnaires obtained by the distribution of questionnaires showed that the strategies carried out by PAI teachers have a significant impact on the results of daily assessments of students.